Climate concerned but anti-nuclear: Exploring (dis)approval of nuclear energy in four European countries. (May 2021) - Sonnberger, Marco; Ruddat, Michael; Arnold, Annika; Scheer, Dirk; Poortinga, Wouter; Böhm, Gisela; Bertoldo, Raquel; Mays, Claire; Pidgeon, Nicholas; Poumadère, Marc; Steentjes, Katharine; Tvinnereim, Endre
Abstract: Energy systems across the world must undergo a fundamental transformation towards the use of low-carbon energy sources and technologies in order to reduce global CO2 emissions. While nuclear energy has historically been highly controversial, especially among people concerned about the environment, some voices have begun to suggest that nuclear energy should be reconsidered as an energy source, to help mitigate climate change. In this study we explore the relationship between climate change concern and public perceptions of nuclear energy, using representative survey data (n = 4048) from four key energy-producing European countries (France, Germany, Norway, and the United Kingdom). After constructing a climate-change concern index and applying multiple linear regression models, we find that climate change concern is associated with more negative perceptions of nuclear energy in all four countries. These negative associations remain when we control for political orientation, gender, age, and education. Thus, a stable pattern of disapproval of nuclear energy among people concerned about climate change seems to exist independently of national contexts. This result casts into doubt the prospect that broad public support could rapidly emerge for the use (or the increasing use) of nuclear energy as a means to ensure reduced carbon emissions.